THE PROBLEMATICS OF THE MEANING OF A CHILD'S STATUS IN NATIONAL LAW: BETWEEN LEGAL CERTAINTY AND JUSTICE - Nurini Aprilianda; Syihabuddin; Guntur Aris Prabowo (CV. RADJA PUBLIKA, 2025)
The article titled